Aplikasi Filantropi Dalam Ekonomi Islam - Herlina, Sri (TIN: Terapan Informatika Nusantara, 2020)
Philanthropy is a concept that has been contained in Islam, which aims for good (al-birr), seeing the different social and economic levels of society, ideas or concepts of philanthropy among people. The effectiveness of philanthropy in reducing social inequality cannot be separated from the role of philanthropic institutions that manage these activities. The potential sourced is one of the alternatives for a community group to reduce the social gap from philanthropy by implementing the distribution of capital to those who cannot afford it, so that it can play a role in economic activity, as a producer in increasing income. Poverty is an interesting theme to discuss, especially among social scientists. Many studies offer solutions to alleviate poverty, but the face of poverty still exists amid the dynamics of changing times. The efforts to tackle the problem of poverty have been continuously carried out by experts throughout the ages in an effort to find the ideal form of poverty alleviation. The theme of poverty is studied not only by developing countries but also developed countries. Before getting to know scientific studies on the problem of poverty, people had carried out a tradition that responded to the problem of poverty in the form of gifts. The activity of "giving" in its various forms is not limited in the form of money or goods but also work or various efforts to ease the burden on the poor and improve their welfare is known as philanthropy. Poverty is an interesting theme discussed, especially among social scientists. Many studies offer solutions to alleviate poverty, but the face of poverty still exists amid the dynamics of changing times. The efforts to tackle the problem of poverty have been continuously carried out by experts throughout the ages in an effort to find the ideal form of poverty alleviation. The theme of poverty is studied not only by developing countries but also developed countries. Before getting to know scientific studies on the problem of poverty, people had carried out a tradition that responded to the problem of poverty in the form of gifts. The activity of "giving" in its various forms is not limited to money or goods but also work or various efforts to ease the burden on the poor and improve their welfare is known as philanthropy. The formulation of the problem in this study is how is the application of philanthropy in Islamic economics? With the aim of research to find out the meaning of philanthropy, to find out the concept of philanthropy in Islam and how is the application of philanthropy in Islamic economics? Today, philanthropy has a number of goals that are not purely religious, but also social and political in nature. For example, there are philanthropic institutions that target only social services, with the belief that providing services, the burden of poverty in society can be reduced or even eliminated. Meanwhile, there are also philanthropic institutions that are engaged in social change, by making social justice their main goal (Sulek, 2010). In other words, these two philanthropic models call for a better social life by paving the way for its realization through a number of economic, political, legal empowerments and so on. Today, philanthropy has a number of objectives that are not purely religious, but also social and political in nature. For example, there are philanthropic institutions that target only social services, with the belief that providing services, the burden of poverty in society can be reduced or even eliminated. Meanwhile, there are also philanthropic institutions that are engaged in social change, by making social justice their main goal (Sulek, 2010). In other words, these two philanthropic models call for a better social life by paving the way for its realization through a number of economic, political, legal empowerment and so on